Corrective Feedbacks and Their Impacts To Learnersâ Uptakes In EFL Speaking Class - Hartono, Didik (EDUCAFL : E-Journal of Education of English as a Foreign Language, 2012)
This paper discusses the importance of both teachersâ and studentsâ acceptance about the fact that errors are important part of learning process. It is through studentsâ errors, teacher can observe what students are trying to posses, what notions students have misunderstood and what additional work they might need. For that reason, errors are often seen as a sign of learning in language acquisition process. On the other hand, teachersâ habits in responding studentsâ spoken errors are varied, showing different reactions they hold towards studentâs spoken errors. Some teachers tend to correct all the errors while some tend to be tolerant, and still some others do not correct at all. Corrective feedbacks are provided by the teacher in responding studentâs errors. From the language teacherâs point of view, the provision of feedback is a major means to inform learners of the accuracy of both their target language production. Unfortunately, sometimes, feedback as a part of teacherlearner interaction in the class is assumed as a barrier in doing a communication. This paper calls the attention to the importance of applying the appropriate corrective feedbacks toward studentsâ spoken errors and the impacts of that error correction behavior toward studentsâ uptake.Keywords: Corrective feedbacks, categories of errors, studentsâ uptake.